Designing A Standard Operating Procedure (SOP) For Restructuring A Language Centre In A Buddhist College - Maria Fransisca Andanti; Bambang Suteng Sulasmono; Mawardi Mawardi (Kelola: Jurnal Manajemen Pendidikan, 2019)
The purpose of the research is designing a Standard Operating Procedure (SOP) in a language centre of a Buddhist college. The SOP was designed as part of the restructuring process of the language centre, aimed at regaining the language centre’s function as a language centre, not language teaching centre as it had been happening. By employing three phases of Branch’s ADDIE (2009), Analyze, Design, and Develop, the study produced an SOP of the language centre’s program that was aimed at guiding the management team to design and implement the programs in language centre based on the three areas of language centre’s activity. The data was gathered through interview, document study, and observation. It then was analyzed through data condensation, data display, and drawing and verification conclusions (Miles, Huberman, & Saldaña, 2014). The SOP focused on three kinds of programs to accommodate the diverse and complex activities the LC should have tackled as a language centre.